ZG16 promotes T-cell mediated immunity through direct binding to PD-L1 in colon cancer - Hui Meng; Wu Yao; Yuhui Yin; Yizhen Li; Yi Ding; Liang Wang; Mingzhi Zhang (BMC, 2022)
Abstract Immunotherapy using programmed cell death 1 (PD1) inhibitors has shown great efficacy in colorectal cancer patients harboring mismatch-repair-deficient (dMMR) and microsatellite instability-high (MSI-H) alterations. We previously showed a negative correlation of zymogen granule protein 16 (ZG16) with programmed death-ligand 1 (PD-L1) expression in patients with colorectal cancer. However, how ZG16 regulates PD-L1 expression is unclear. In this study, we showed that ZG16 can directly bind to glycosylated PD-L1 through its lectin domain, leading to PD-L1 degradation. Mutations on the lectin domain of ZG16 largely inhibit the interaction between ZG16 and PD-L1. Importantly, ZG16 overexpression suppressed tumor growth in two syngeneic mouse models through blockage of PD-L1 expression in cancer cells meanwhile suppression of PD1 expression in T cells. We also showed that ZG16 could improve the effect of chemotherapy and may be delivered as a protein to serve as an immune checkpoint inhibitor to promote T-cell mediated immunity.